Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika Berbentuk Cerita pada Pokok Bahasan Keliling dan Luas Lingkaran Kelas VIII MTs Negeri Ngemplak Tahun 2015/2016 - Anggraeni, Melindawati Kusuma, Dra. Sri Sutarni, M.Pd (2016)
This research is aimed at describing the learners' error in finishing the mathematic questions with the main discussion of the perimeter and the circle area in the form of story, the research was taking place at the class VIII MTs Ngemplak in academic year 2015/2016. This research uses qualitative descriptive method. The data collection technique uses test, interview, and documentation methods. The credibility of the data uses the triangulation technique that is comparing between the result of the test and the result of the interview. The data analysis has phases namely: data reduction, data presentation, and conclusion taking. based on the data analysis and the discussion the learners had experienced several mistakes such as; the error in understanding a problem Comprehension Errors (C) that is a mistake experienced by the learners in understanding a story problem about the language meaning interpretation and to give a meaning to a picture in the stoty problem, the error of question transformation or Transformation Errors (T) that is learners are able to understand what has already become a question to be found but are unable to identify the operation or the sequence of the operation is needed to solve the problem, the error in doing the computation that is the error experienced by the learners in doing the calculation to finish the mathematic questions in the form of story problem, the error in writing the final answer or Encoding Errrors (E) that is learners correctly solve the solution of a problem but are unable to define solution in the form of correct notation.